2021
DOI: 10.1093/comjnl/bxaa175
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Multi-Channel EEG Filtering Method for Ocular and Muscular Artifact Removal Based on the 3D Spline Interpolation Technique

Abstract: The present work develops a novel hybrid method for ocular and muscular artifact removal from electroencephalography (EEG) signals, EFICA-TQWT. It is a combination of efficient fast independent component analysis (EFICA) method with the tunable Q-factor wavelet transform (TQWT). The main contribution of this paper is to apply the 3D interpolation method in the filtering system. Three EEG datasets are used in this work, two healthy and one epileptic. The choice of subjects for each dataset is made with the help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Defective channels are identified and mitigated through interpolation [37]. The interpolated EEG signal ζ(t) can be obtained as follows:…”
Section: As X = (16)mentioning
confidence: 99%
“…Defective channels are identified and mitigated through interpolation [37]. The interpolated EEG signal ζ(t) can be obtained as follows:…”
Section: As X = (16)mentioning
confidence: 99%
“…Devulapalli et al [99] introduced a hybrid method firefly-Levenberg-Marquardt (FLM) with adaptive filter for optimization of EMG, ECG, EOG artifacts and demonstrated that this method is effective in removal of ocular artifact. Abidi et al [100] has shown a hybrid method for removal of muscle and ocular artifacts for multi-channel EEG with efficient fast independent component analysis (EFICA) and tunable Q-factor wavelet transform (TQWT) with reduced mean square error. Chen et al [101] proposed variational mode decomposition (VMD) with CCA for removal of muscle artifact and demonstrated that it is superior method compared to the available methods.…”
Section: Performance Metricmentioning
confidence: 99%
“…Currently, artifact detection or removal is also addressed using machine learning and deep learning models considering it as hybrid artifact removal methods. SVM combined with other artifact removal technique is the most widely used hybrid method as indicated in [27,68,97,100] , [135−138]. Extreme learning machine algorithm using regression model is proposed in [139] for reducing the cardiac artifact of single channel EEG.…”
Section: 2machine Learning and Deep Learning Models For Artifacts Han...mentioning
confidence: 99%
“…To determine whether there is an obvious gap between the data of the three arrays, this paper uses the spline function interpolation method [29] to fit them into three-dimensional surface graphs, respectively, as shown in Figure 3 (in this paper, only 01 and 02 gestures are selected, and 03 is similar, so we will not repeat them). The x-direction represents the first-dimension information of the feature, and the value range is 1 to 192.…”
Section: Error Correction Algorithm Based On Convolution Layermentioning
confidence: 99%